The impact of meteorological changes on the quality of life regarding thermal comfort in the Amazon region - Santos, Adrian Felipe dos; Moura, Flávio Rafael Trindade; Seruffo, Marcos César da Rocha; Santos, Waldeir Pereira dos; Costa, Gabriel Brito; Costa, Fernando Augusto Ribeiro (Frontiers in Climate, 2023)
The meteorological imbalances in Brazil have a strong impact on the lives of the population across the country, especially in the Amazon region. These impacts extend to meteorological phenomena, such as extreme rainfall, droughts, and an increase in temperature in several regions, as well as impacts on health, the economy, and, as the object of this study, the quality of life. This study presents the impact of meteorological changes on the quality of life in the Amazon region, based on (i) the thermal discomfort index (TDI), (ii) the temperature and humidity index (THI), and (iii) the effective temperature index as a function of the wind (TEFW). For this, meteorological data from the years 2003–2021 were used, in which the variables include total precipitation, global radiation, air-dry bulb temperature, the maximum temperature in the previous hour, the minimum temperature in the previous hour, relative humidity, and wind speed. This analysis indicates that for this tropical region, the sensation of mild discomfort was predominant in about 70% of the measurements, indicating a certain level of impact on the population's quality of life, in addition to the fluctuation of levels of discomfort during periods of winter in that there are high rates of precipitation. The data control was performed with the removal of null data and calculation of monthly and annual averages, by using the compression (average) empty data frames in order to receive the values without losing the indexing of dates. At first, it was considered to use the kriging process to fill in the missing data; however, due to the existence of microclimates in the regions, the data could characterize remote regions in a generalized way, which would make it difficult to understand these data in comparison with the data from the National Institute of Meteorology (INMET, in Portuguese).